Pengembangan Media Audio Visual Berbasis Film Pendek pada Materi Teks Anekdot pada Kelas X SMK Bina Taruna 2 Medan - Sarah, Ade; Ali, Ali; Rita, Rita (Sintaks: Jurnal Bahasa & Sastra Indonesia, 2024)
This study aimed to develop and assess the feasibility of short film-based audio-visual learning media for anecdotal text material in class X SMK. The population and sample included 31 students, utilizing the Research and Development (R&D) approach. Following the ADDIE model's five steps—analysis, design, development, implementation, and evaluation—the results indicated the media's validity and suitability for class X SMK students, as determined by media and material experts. Media expert I assessed it as 90% "very appropriate," media expert II as 86% "very eligible," material expert I as 85% "decent," material expert II as 82% "decent," and teacher's assessment as 94% "very feasible." Tested in SMK Bina Taruna 2 Medan, it received 88% "very feasible." In conclusion, the short film-based audio-visual learning media for anecdotal text material is deemed suitable for class X SMK, serving as an effective learning medium.